2020
DOI: 10.1016/j.jinf.2020.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection of SARS-CoV-2 and Influenza virus in Early Stage of the COVID-19 Epidemic in Wuhan, China

Abstract: Co-infection of SARS-CoV-2 and Influenza virus in EarlyStage of the COVID-19 Epidemic in Wuhan, China

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 7 publications
1
59
0
Order By: Relevance
“…We also detected multiple co-detection of SARS-CoV-2 with other respiratory viruses, such as influenza A and B and human metapneumovirus, which have also been reported elsewhere 40,41 . Although, co-infections with other respiratory viruses have been reported in other countries 40,42,43 , no difference in clinical disease severity between cases with and without viral co-infection has been observed thus far 44 . The co-circulation of other respiratory pathogens highlights the need to scale up laboratory and molecular screening of SARS-CoV-2 and other respiratory viruses in public laboratories across Brazil 15 .…”
Section: Discussionmentioning
confidence: 89%
“…We also detected multiple co-detection of SARS-CoV-2 with other respiratory viruses, such as influenza A and B and human metapneumovirus, which have also been reported elsewhere 40,41 . Although, co-infections with other respiratory viruses have been reported in other countries 40,42,43 , no difference in clinical disease severity between cases with and without viral co-infection has been observed thus far 44 . The co-circulation of other respiratory pathogens highlights the need to scale up laboratory and molecular screening of SARS-CoV-2 and other respiratory viruses in public laboratories across Brazil 15 .…”
Section: Discussionmentioning
confidence: 89%
“…have report the symptoms of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection -named coronavirus disease 2019 (COVID-19)- appear very similar to influenza. 1 We would like to share our findings for SARS-CoV-2 and influenza virus infections as virus co-circulation is likely to occur in future. 2 It is important to facilitate differential diagnosis.…”
mentioning
confidence: 72%
“… 9 In contrast, another study only reported mild symptoms in limited coinfection outpatients. 10 A retrospective study found that the coinfection rate of SARS‐CoV‐2 and influenza virus was as high as 57.3% (among which 49.8% was coinfected with IAV) in a single‐centered study of 307 COVID-19 patients during the outbreak period in Wuhan. 11 Thus, the high coinfection rate and the unpredictable clinical outcomes pose great concerns when facing the threat of both viruses.…”
Section: Introductionmentioning
confidence: 99%